Alternative energy sources for seawater desalination. (20th November 2007) - Misra, B.M.
This paper deals with the role of nuclear energy for large-scale economic production of fresh potable water from seawater. It also deals with the environmental and sustainability aspects of different desalination processes using various energy sources. Water cost-reduction strategies in nuclear desalination plants are particularly discussed in the paper.